2019
DOI: 10.1016/j.biocon.2019.02.012
|View full text |Cite
|
Sign up to set email alerts
|

What explains variation in the strength of behavioral responses to predation risk? A standardized test with large carnivore and ungulate guilds in three ecosystems

Abstract: If access to food is affected by the risk of predation, then the number of individuals killed by predators is an incomplete measure of the limiting effect of predation. Nonetheless, it is often assumed that the costs of antipredator responses (risk effects) are either small enough to be ignored or positively correlated with direct predation, and thus unlikely to alter inferences based on predation rates. These assumptions are rarely tested. Here we studied five large carnivores and ten prey species in three Za… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 50 publications
(78 reference statements)
1
33
0
Order By: Relevance
“…The growing emphasis on developing a better understanding of the interactions among multiple prey and predators within large carnivore—ungulate systems 15 , 26 , 57 is being driven, in part, by new methodologies to study behavior 10 . For example, using ABRs enabled us to test responses to playbacks during night and day on numerous species 38 .…”
Section: Discussionmentioning
confidence: 99%
“…The growing emphasis on developing a better understanding of the interactions among multiple prey and predators within large carnivore—ungulate systems 15 , 26 , 57 is being driven, in part, by new methodologies to study behavior 10 . For example, using ABRs enabled us to test responses to playbacks during night and day on numerous species 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Both variables describing human land use had strong effects on the probabilities of typical vs. fast movement. Outside the National Park in the GMAs (where prey density is known to be lower 63 , 66 ), wild dogs were significantly more likely to adopt the fast movements of State 3 (Figs. 6 and 7 C).…”
Section: Resultsmentioning
confidence: 99%
“…Faster movements in GMAs relative to the National Park probably have at least two causes. First, the densities of large herbivores are lower in the GMAs 62 , including impala and puku, which are most important prey of African wild dogs in the Luangwa Valley 66 . Lower prey density would be expected to translate into increased effort to locate and kill prey.…”
Section: Discussionmentioning
confidence: 99%
“…Wildebeest, were less likely to flee from these threats, instead appearing to offset this response by increasing the amount of time spent monitoring the danger. The use of complementary anti-predator responses such as this would not have been detected if we had only examined a single behavioral metric (see [ 68 70 ]). Several authors have noted that anti-predatory behaviors should decrease levels of direct predation to the point that lethality becomes a poor proxy for predation threat [ 64 , 71 ], and studies in other large herbivore communities found that capture success fails to predict proactive anti-predator avoidance behaviors (e.g., [ 72 ]) and reactive levels of vigilance to predators within 0.5 km [ 59 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…The physical and social environments may also shape anti-predator decision-making [ 57 , 68 , 70 ]. The distribution of resources across the landscape differs for browsers and grazers, forcing certain species to enter habitats of varying complexity [ 59 ] and/or that differ in underlying predation risk [ 57 ].…”
Section: Discussionmentioning
confidence: 99%